Revisiting Cementoblastoma with a Rare Case Presentation - Vijayanirmala Subramani; Malathi Narasimhan; Suganya Ramalingam; Soumya Anandan; Subhashini Ranganathan (Case Reports in Pathology)
Cementoblastoma is a rare benign odontogenic neoplasm which is characterized by the proliferation of cellular cementum. Diagnosis of cementoblastoma is challenging because of its protracted clinical, radiographic features, and bland histological appearance; most often cementoblastoma is often confused with other cementum and bone originated lesions. The aim of this article is to overview/revisit, approach the diagnosis of cementoblastoma, and also present a unique radiographic appearance of a cementoblastoma lesion associated with an impacted tooth.